Adjuvants targeting innate T lymphocytes for improved oral vaccination - ALBUTTI, AQEL SULAIMAN (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2019)
Effective mucosal vaccines can provide protective local and systemic immunity. Oral vaccination in particular has the potential to offer a safer and more efficacious approach than injection-based approaches, especially in developing countries. Nevertheless, in general, antigen delivery via the oral route triggers weak immune responses or immunological tolerance. The effectiveness of oral vaccination can be improved by co- administering adjuvants. However, a major challenge is the absence of potent and safe oral adjuvants for clinical application. A second obstacle is that responses to oral vaccines vary between developed Western countries and developing countries where they are often less effective. This may be attributed in part to nutritional deficiencies including a limited intake of factors including vitamins, impacting on the microbiome and the generation of specific metabolites. Here, evidence is provided that supplementation with a specific vitamin can enhance immune responses to oral vaccines against Travellers diarrhoea and cholera. Secondly, data are presented showing a novel approach for targeting invariant natural killer T cells to enhance intestinal and systemic immune response after oral vaccination. Overall this thesis presents two novel strategies to enhance the effectiveness of oral vaccines for enteric diseases.
APPROVED